Penerapan Model Pembelajaran Kooperatif Tipe Group Investigasi Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Kelas VI SDN No. 1 Labuan Bajo - Yupin Aliwu; Amiruddin Hatibe; Amram Rede (Universitas Tadulako, 2016)
The research was conducted on even semester in SDN No.1 Labuan Bajo in academic year 2014-2015. The problems of the study was how the implementation of cooperative learning model by group investigation to improve activity and learning outcomes in science subjects at grade sixth. The research was used classroom action research by 2 cycle. Each cycle consists of 2 meetings. The results of research showed that both the average of teacher and students activity were in good categories. Furthermore, the results of achievements consisted of classical absorption value and classical learning completeness. Based on indicators, classical absorption value clarified was attained with good category and classical learning completeness had over of indicators that settled of School, and to have excellent category. Based on the redearch results, they can concluded that the implementation of cooperative learning model by Group Iinvestigation could increase the activity and learning outcomes at grade sixth SD No.1 Labuan Bajo.